Yoga Virtual Sebagai Metode Dharma Sadhana Guna Meningkatkan Kesehatan Spiritual Masyarakat Di Tengah Masa Pandemi Covid-19 - Made G. Juniartha; Putu Ayu Sri Kumala Dewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
During the Covid-19 pandemic, health is very important to maintain, not only physical and mental health, spiritual health is also increasingly being considered as a necessity. For this reason, yoga provides a way of overall health for humans. Yoga activities during the pandemic have not subsided by yoga practitioners. Various sharing efforts have been made by yoga teachers and yoga practitioners, from using the media Youtube, Facebook, Instagram, Zoom-meeting, Webex-meeting, and various other media to the appearance of a virtual yoga activity. This virtual yoga activity is also included in one of the six Hindu guidance methods, namely dharma sadhana. As an effort to guide mankind to achieve happiness and harmony in life through yoga in the midst of the Covid-19 pandemic, various social media portals available on the internet are maximized for their functions by yoga practitioners and practitioners so that they can be connected to one another without reduce the meaning of the yoga activity. Based on the author's search results on social media portals regarding virtual yoga activities, it can be concluded that in order to obtain good spiritual health it can be said that practicing yoga during the Covid-19 pandemic greatly affects the spiritual health condition of yoga practitioners.Keywords: Virtual Yoga; Dharma Sadhana; Spiritual Health.